Quinacrine (mepacrine) action at frog end-plate. - Adams, P R (1980)
1. The effects of quinacrine on end-plate currents (e.p.c.s.), miniature end-plate currents (m.e.p.c.s.) and ionophoretic responses at voltage clamped frog end-plates were investigated. 2. A quinacrine concentration (2 microM) that by itself has little effect on m.p.e.c.s. will considerably attenuate responses to bath applied carbachol. The combined effect of the two drugs causes the m.e.p.c.s. to disappear. 3. The depressant effect of quinacrine on ionophoretic responses to carbachol or acetylcholine is increased in acid solutions and decreased in alkaline solutions, suggesting that quinacrine is active as an acridinium ion. 4. Quinacrine (2-10 microM) causes a use-dependent block of end-plate channels which manifests as an inhibitory effect of an ionophoretic prepulse on the response to a test pulse. The inhibitory interaction decays exponentially with a time constant tau s that depends on the nature of the agonist used for the prepulse, on the quinacrine concentration, and on the membrane potential. 5. Quinacrine (5-20 microM) reduces the amplitude of e.p.c.s. and m.e.p.c.s. It also increases the rate of decay of the e.p.c. or m.e.p.c. tails, which remain exponential. The decay rate constant 1/tau f increases linearly with quinacrine concentration both in the presence and absence of 3 microM-neostigmine. The slope of this linear relation increases slightly with membrane hyperpolarization. 6. These data suggest that quinacrine's main action is a slow, voltage dependent blockade of open end-plate channels, though there are probably additional effects on acetylcholinesterase and channel opening. In accordance with the open channel blocking model, 1/tau s and 1/tau f both increase linearly with quinacrine concentration. However, the slopes of these lines lead to rather different estimates of the forward blocking rate constant (8 X 10(7) and 4 X 10(8) M-1 S-1 respectively). 7. The unblocking rate constant is about 5 S-1 at -80 mV. It is much more voltage dependent than the forward rate constant.